Upaya penyelesaian masalah pemantapan kawasan hutan pada taman nasional di Pulau Sumatera - Desmiwati; Surati (Foresty Faculty of Hasanuddin University, 2017)
In the frame of the implementation of good forest management, the certainty of the factually and legally forest area it is needed in order in order to have solid legal foundation. This means the stability on forest boundary areas it is required. This study aimed to carry out scrutiny of the stability of 11 national parks areas in Sumatra, and to recognize the development of stabilization of national parks. The study is conducted in 11 national parks in Sumatra consisting of 7 national parks as conservation forest management unit (CFMU) and 4 parks are not CFMU. The analysis approach used for the research was qualitative descriptive. The results showed that out of 11 national parks only 27.27% which has been structuring the outer boundary from end to end, meanwhile 72.72% have not done. This is because there are some boundaries areas that will be regulated still have problems with the community. Zonation structuring has been conducted by 10 National Park (90.91%) but 1 TN (9.09 have not done the zonation structuring yet). There are some national parks has not been define the boundary properly. Out of number of issues, some efforts that need to be done are to clarify boundary markers on the national parks that can be recognized by all stakeholders, the the acceleration of zone marking and carried out in accordance with the interests of all stakeholders, as well as the need for community involvement in the management of national parks.